Development of Qur'an memorization model in shaping religious character based on integrative AIK - Hermawan, Hermawan; Firdaus, Firdaus (UIN Salatiga, 2025)
The Qur'an, as the unchangeable word of Allah, forms the foundation of a Muslim's religious life. The act of memorizing the Qur'an (Tahfidzul Qur'an) is a core spiritual practice vital for developing strong religious character based on integrative AIK, which serves as essential social capital for problem-solving in society. This qualitative research aimed to three-fold: to identify the Tahfidzul Qur'an training model, to analyze the process of religious character formation based on integrative AIK via the program, and to pinpoint the enabling and hindering factors at the Darul Arqom Muhammadiyah Islamic Boarding School in Jono Bayan, Purworejo. The research gathered data from key informants, including teachers, caregivers, three supervisors, and four students, using observation, interviews, and documentation. The results show that the training model successfully integrates habit-forming routine based on integrative AIK, reward systems, and a personalized approach for students. The program is significantly supported by robust institutional management and clear delegation of authority to the instructional staff. Conversely, key inhibiting factors that challenge character formation include a lack of sufficient supervisors, scheduling conflicts between mentors and students, and student exhaustion due to demanding school activities.